Psychological background underlying the quality of Croatian students' roommate relationship - Roje, Luka (Array, 2014)
This study was created as a framework for website idealni-cimer.hr, an internet interface that uses psychology-grounded instruments to help students find their suitable rommate within half an hour, making the rommate search quick and effective. The results of American research could potentially lead us to wrong conclusions when searching for an ideal rommate of a Croatian student, since findings seem to be culturally specific. A pilot study and the analyses of focus groups done on 120 Croatian students, suggested that personality is not the only predictor of satisfaction with the roomate relationship. Attitudes toward neatness and the life habits while in a shared apartment also proved to be important. Based on these findings, we designed and assembled a questionnaire and examined its diagnostic validity on a sample of 80 students who were living with a roommate at the time of the study. Analysis that included data of over 300 users of the idealni-cimer.hr interface suggested that the key determinants of roommate relationship satisfaction are attitudes toward neatness, several personality dimensions (consciousness, self-discipline, cooperation, extraversion, and neuroticism) and specific life habits (behavior concerning common life space, behavior concerning relationship to the rommate, and bringing over guests in the common space).